The Criminal Protection for the duty of marital sincerity from the crime of adultery - DRIF, Chouaib (Journal of Human Sciences, 2020)
Islamic law called for the necessity of marriage and led it to be loved for the reason that it is the safest way to discharge the sexual instincts and to maintain the descent. In return, they criminalized any behaviour that intends to abuse the duty of the marital loyalty particularly when the matter is related to the crime of adultery which is considered from the most dangerous crimes that stops the confidence between the married couple. the Algerian legislator tended to criminalize the adultery act for the preservation of the sacredness of the marital bond. In fact, reality reveals the reverse because this crime is in constant increase which reflects the deficiency of the criminal protection that the legislator implemented in order to repulse the danger of this crime. Hence, it was compulsory that the Algerian legislator has to revise these texts to confront the adultery crime and to achieve the stability of relations between the married couple. This would be achieved by affording an objective, measuring and real protection which is applicable with the privacy of the Algerian family, which is based on Islamic principles.